DEVELOPING AND VALIDATING THE ELEMENTARY STUDENT LEARNING AGILITY SCALE (ESLAS) FOR MEASURING KEY LEARNING TRAITS IN ELEMENTARY EDUCATION - Kusumawati, Tri Harum; Herwin, Herwin (University of Kuningan, 2024)
This study aimed to develop elementary student learning agility scale (ESLAS) to measure elementary school students’ perseverance, tenacity, interest, and independence in accomplishing learning process. This study also focused on examining translational validity and internal consistency reliability to construct a valid and reliable scale. There were 90 elementary students chosen using voluntary random sampling as the respondents and five experts invited as the validators. The study developed ESLAS using a five-point Likert’s scaling method with twenty items measured. Data obtained from ESLAS were used to examine internal consistency reliability while data from validation sheet were used to judge content validity index (CVI) and content validity ratio (CVR). Results showed that the developed ESLAS was considered very valid by the validators (CVI = +1.00, CVR = 1.00) and was categorized in a very high reliability (Cronbach’s α = .879). Another result depicted that there was no negative value in inter-item correlation, meaning that all items measured similar construct. The results implied that the developed ESLAS is considered as a valid and reliable scale to measure elementary students’ learning agility.